2020
DOI: 10.1093/ibd/izaa052
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Change in Inflammatory Aspects of Diet and Change in IBD-related Inflammation and Symptoms Over 1 Year: The Manitoba Living With IBD Study

Abstract: Background We aimed to investigate (1) the stability of inflammatory aspects of diet over 1 year among persons with inflammatory bowel disease (IBD) and (2) the impact of change in diet on changes in inflammation and IBD symptoms over 1 year. Methods Participants were recruited to the Manitoba Living with IBD Study and completed the Harvard Food Frequency Questionnaire (FFQ). The Dietary Inflammatory Index (DII) and the Empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Age and disease duration groups were created for consistency with other studies from the IBD cohort. 22,23…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age and disease duration groups were created for consistency with other studies from the IBD cohort. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent was obtained from all participants after the nature of the procedure(s) had been explained. Participants in the Manitoba Living With IBD Study 22 had experienced IBD‐related symptoms during the 2‐year period before recruitment and were at least 18 years old 23 . Participants were enrolled between June 2015 and May 2017 and completed a web‐based survey every 2 weeks for 1 year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have also been some studies examining the effect of the inflammatory potential of the diet, as measured by a score, on gut inflammation and disease activity in patients already diagnosed with IBD, but both positive and null relationships have been reported [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two large recent prospective cohort studies indicated an association between dietary patterns with a high inflammatory potential and an increased risk of CD [5,10]. In addition, several other caseecontrol studies have suggested that the inflammatory potential of diet may be associated with the disease severity in patients with CD [11,12], but these studies were observational and did not explore the underlying mechanisms behind the inflammatory potential of diet in CD.…”
Section: Introductionmentioning
confidence: 99%